An in vitro tumorigenesis model based on live-cell-generated oxygen and nutrient gradients - Anne C. Gilmore (Nature Portfolio, 2021)
Gilmore et al. describe an in vitro tumorigenesis model that produces cell-generated gradients of oxygen and nutrients. Its 2D configuration simplifies live cell, immunofluorescent, and microscopic interrogation of cancer cell behaviour in differentially developed tumour microenvironment conditions, including co-culture systems.